Nekateri vidiki uporabnosti dihalnih strategij v vzgojno-izobraževalnem delu - Cerar, Katarina (Šport (Ljubljana), 2013)
One of the fundamental objectives of modern educational process is to teach students to think critically and effectively (Rupnik Vec, 2010, Peklaj et al.,2009). Critical thinking is the basis for many key competences that shouldbe developed by the young people during their compulsory education and training. Modern teaching practice in the European Union aims to fulfill these new role and task: creating critical thinkers (Uradni list EU, 2006). Research shows that students' competence development is highly dependent on their perception of their teacherćs competence (Peklaj et al., 2009). If teachers are to develop critical thinking skills in theirs students, this ability should be continuously developed by themselves. Existing conceptual tools (Rupnik Vec, 2006), which can be used to develop critical thinking capacity could be complemented by strategies that include controlling and detection of breathing (respiratory strategy). Kinesiological science could act as a scientific field, which would allow the development of appropriate forms of respiratory strategies and methods that would be suitable for use in educational work.
Keywords: breathing exercises; critical thinking; dihalne vaje; education; edukacija; kritično mišljenje; meditacija; meditation; samorefleksija; self-reflection; sport; šport